Learning a foreign language though speaking - Voronova, Ye. M.; Воронова, Є. М.; Воронова, Е. М. (Харківський національний автомобільно-дорожній університет, 2020)
The article shows the importance of the goal clarity at the English lesson in the technical university. The goal of a foreign language lesson is outlined in the article as an essential component of mastering speech and a means of learning a foreign language. It is underlined that speech activity should be carried out on two levels. The article emphasizes the need to bring to each student that it is impossible to teach speech activity, only the student himself can learn it.
Вивчення іноземної мови через мовну діяльність
Изучение иностранного языка посредством речевой деятельности
Keywords: goal clarity; essential component; speech activity; means of learning; compulsory aspects; goal; чіткість мети; суттєвий компонент; мовленнєва діяльність; засоби навчання; обов’язкові аспекти; мета; ясность цели; существенный компонент; речевая деятельность; средства обучения; обязательные аспекты; цель; 372.881.111.1